Artificial intelligence based on falling in older people: A bibliometric analysis - Yenisehir, Semiha (Wiley, 2024)
ObjectivesThis study aimed to analyze publications on artificial intelligence (AI) for falls in older people from a bibliometric perspective.MethodsThe Web of Science database was searched for titles of English-language articles containing the words artificial intelligence, deep learning, machine learning, natural language processing,, neural artificial network, fall, geriatric, elderly, aging, older, and old age. An R-based application (Biblioshiny for bibliometrics) and VOSviewer software were used for analysis.ResultsThirty-seven English articles published between 2018 and 2024 were included. The year 2023 is the year with the most publications with 16 articles. The most productive research field was Engineering Electrical Electronic with seven articles. The most productive country was the United States, followed by China. The most common words were injuries, people, and risk factors.ConclusionPublications on AI and falls in the elderly are both few in number and the number of publications has increased in recent years. Future research should include relevant analyses in scientific databases, such as Scopus and PubMed. The English-articles based on artificial intelligence and falls in the older people are both few in number. The number of publications has increased in recent years according to technological developments. In future research, relevant analyzes should be conducted in scientific databases, such as Scopus and PubMed.image
Keywords: artificial intelligence (AI); falling; geriatrics; older adults; web of science (WoS)